IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM ATTITUDE ASSESSMENT IN INDONESIAN LANGUAGE LEARNING: A CASE STUDY OF SMA NEGERI 3 SURAKARTA - Afrizal Mufti (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
One of the components in the implementation of learning is the assessment process. In this case, attitude assessment, as a measuring tool to find out the level of development and progress of students in the learning process. Of course, the independent curriculum as a new product of 21st century education provides many opportunities and inputs so that the implementation of learners in the future will be better. The focus in this study is related to the attitude assessment process carried out by teachers in Indonesian subjects. The purpose of this study is to determine the application of attitude assessment carried out by teachers of Indonesian language subjects and implementation to students. In analyzing data using qualitative methods with a descriptive approach, the design used is a case study, so that researchers are able to uncover and analyze problems in depth and get more specific results. The subjects in this study were Indonesian language teachers, students of classes X, XII, XII. Data collection using primary and secondary sources. Primary sources of sources such as observations, interviews, while secondary sources are books, journals, and scientific articles. The result of this study is that the application of attitude assessment is classified as good by dividing the attitude assessment pattern by adjusting the application of pancasila student profile values at each level so that each grade level can be focused on the assessment process of one aspect among the six aspects of pancasila student profile values. Some of the obstacles encountered in attitude assessment start from the quantity and efficiency of assessment time that is not optimal.